2019
DOI: 10.3390/socsci8060180
|View full text |Cite
|
Sign up to set email alerts
|

Arrest and Referral Decisions in Sexual Assault Cases: The Influence of Police Discretion on Case Attrition

Abstract: Research on sexual assault case attrition spans from the decision of victims to report the incidents and cooperate with police during investigations through the final case disposition in the courtroom. However, few studies have focused on how police discretion influences attrition at the points of arrest and case referral. The current study examines factors of adult sexual assaults reported to the police to determine which legal and extralegal factors were predictive of arrest and which variables were predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
(131 reference statements)
0
12
0
Order By: Relevance
“…Canada and the United States share similar correlates of arrest in sexual assault investigations, and thus, Data from studies were largely collected from locations classified as urban or suburban, with only Morabito, Williams, & Pattavina (2019) analyzing data from multiple sites including rural jurisdictions. Importantly, several studies shared data sources from the Los Angeles Police Department and Sheriff’s Department (Kaiser et al, 2017; O’Neal et al, 2019; Spohn & Tellis, 2019), a large Midwestern police department (Alderden & Ullman, 2012a, 2012b), and a midwestern police department (Wentz, 2019; Wentz & Keimig, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Canada and the United States share similar correlates of arrest in sexual assault investigations, and thus, Data from studies were largely collected from locations classified as urban or suburban, with only Morabito, Williams, & Pattavina (2019) analyzing data from multiple sites including rural jurisdictions. Importantly, several studies shared data sources from the Los Angeles Police Department and Sheriff’s Department (Kaiser et al, 2017; O’Neal et al, 2019; Spohn & Tellis, 2019), a large Midwestern police department (Alderden & Ullman, 2012a, 2012b), and a midwestern police department (Wentz, 2019; Wentz & Keimig, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, studies have found a significant correlation between arrest and victim alcohol consumption (O'Neal et al, 2019;Venema et al, 2019), victim credibility (Alderden & Ullman, 2012b;Kaiser et al, 2017;, intimate partner relationships (Alderden & Ullman, 2012b;Kaiser et al, 2017;, nonstranger relationships (Alderden & Ullman, 2012b;, and victim race Venema et al, 2019). Nonetheless, other studies found victim credibility measures (Kaiser et al, 2017;O'Neal et al, 2019;Spohn & Tellis, 2019), victim alcohol consumption (Scott & Beaman, 2004;Wentz & Keimig, 2019), suspect race (Alderden & Ullman, 2012a;Kaiser et al, 2017), victim race (Kaiser et al, 2017;Spohn & Tellis, 2019), intimate partner relationships (O'Neal et al, 2019;Spohn & Tellis, 2019), and nonstranger relationships (Kaiser et al, 2017;O'Neal et al, 2019;Spohn & Tellis, 2019) were not significantly correlated with arrest.…”
Section: Perceptual Shorthandmentioning
confidence: 98%
See 3 more Smart Citations